Coumarin-derivatized fluorescent vic-dioxime-type ligand and its complexes; the preparation, spectroscopy, and electrochemistry - ÖZKAYA, ALİ RIZA (SPRINGER, 2007)
A new vic-dioxime bearing coumarin functionality, N-'1, N-'2-Dihydroxy-N1, N2-bis(4-methyl-2-oxo-2H-chromen-7yl) oxalimidamid (LH2), N,N-bis-[4-methylcoumarinyl]-diamino glyoxime (LH2), and its mono- and dinuclear complexes {copper(II), cobalt(II), nickel(II) and uranyl(II)} have been reported. The. uorescence excitation and emission spectra of LH2 and its complexes with metal ions were examined. It was observed that. uorescence and excitation emission intensity of LH2 was quenched depending on complex formation with metal ions. The characterizations of all newly synthesized compounds were made by elemental analysis, H-1-n.m.r,i.r.,u.v.-vis., and l.c-m.s. m.s. data. Electrochemical behaviour of the ligand involving oxime and coumarine moieties, and its complexes with Ni-II, Cu-II, Co-II and UO2II were investigated by cyclic voltammetry. The comparison of the electrochemical behaviour of the ligand with its complexes enabled us to identify metal-, oxime- and coumarine-based signals.
Keywords: TRANSITION-METAL-COMPLEXES; TRINUCLEAR COMPLEXES; DINUCLEAR COMPLEXES; REDOX PROPERTIES; LIQUID-CRYSTALS; NI COMPLEX; (E,E)M M; NICKEL(II); MONO; MONONUCLEAR